Analisis Usaha Peternakan Ayam Broiler pada Peternakan Rakyat di Desa Karya Bakti, Kecamatan Rungan, Kabupaten Gunung Mas, Provinsi Kalimantan Tengah - Yemima Yemima (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
This study aims to determine the broiler chicken farm income on household scale farm Karya Bakti Village, Rungan subdistrict, Gunung Mas, Central Kalimantan and to determine the feasibility of their business. This study used a descriptive quantitative methods and techniques of data collection by observation and interview.. The results of this study has get incomes Rp.8.450.461,33 /period and R/C ratio of 1.698. Thereby the broiler farm business in Karya bakti village elegible to be developed.